2018
DOI: 10.1002/mnfr.201700503
|View full text |Cite
|
Sign up to set email alerts
|

Camelina Sativa Oil, but not Fatty Fish or Lean Fish, Improves Serum Lipid Profile in Subjects with Impaired Glucose Metabolism—A Randomized Controlled Trial

Abstract: A diet enriched in CSO improves serum lipid profile as compared with a diet enriched in FF or LF in subjects with impaired fasting glucose, with no differences in glucose metabolism or concentrations of inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 55 publications
5
88
1
3
Order By: Relevance
“…The camelina oil consumption was 25.7 ± 2.7 g per day in the CSO group. Dietary intakes have been reported in detail elsewhere . The proportion of ALA (18:3n‐3) in plasma phospholipids increased in CSO group ( p < 0.001) and differed significantly from the other groups.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The camelina oil consumption was 25.7 ± 2.7 g per day in the CSO group. Dietary intakes have been reported in detail elsewhere . The proportion of ALA (18:3n‐3) in plasma phospholipids increased in CSO group ( p < 0.001) and differed significantly from the other groups.…”
Section: Resultsmentioning
confidence: 80%
“…There were no differences in baseline characteristics among the study groups ( Table ). Reported physical activity of the subjects did not change during the study . The average number of fish meals per week was 4.4 ± 0.4 in the FF, 4.3 ± 0.5 in the LF, 0.9 ± 0.4 in the CSO, and 0.9 ± 0.4 in the control group during the study.…”
Section: Resultsmentioning
confidence: 89%
“…Recruitment and characteristics of the subjects have previously been described (Schwab et al, ). The main inclusion criterion was fasting plasma glucose concentration 5.6–7.0 mmoL/L.…”
Section: Methodsmentioning
confidence: 99%
“…The study diets were isocaloric and they were based on current nutrient recommendations (Becker et al, 2004;Perk et al, 2012) excluding fish and ALA intakes. Details of study diets have been reported (Schwab et al, 2018). The fatty fish group consumed four fish meals of fatty fish (e.g.…”
Section: Study Dietsmentioning
confidence: 99%
“…The strengths of the current study include a randomized controlled study design and good 338 compliance with study diets, as previously reported [25]. However, there are also some 339 limitations to consider.…”
mentioning
confidence: 92%